OPTIMASI PROSES PEMBUATAN BIODIESEL DARI ASAM LEMAK SAWIT DISTILAT (ALSD) DAN DIMETHYL CARBONATE (DMC) MENGGUNAKAN KATALIS NOVOZYM®435 - William, Johan Senjaya, Taslim, Tjahjono Herawan, Meta Rivani (Universitas Sumatera Utara, 2016)
Biodiesel production has rapidly grown over the last decades, and it has attracted much attention in the market as fuel that promising substitute for petroleum diesel, because its physical and chemical properties and energy content are similar to those of petroleum diesel. The main problem in producing biodiesel is its high cost which could be reduced by use of less expensive feedstock. Therefore, in this work biodiesel is synthesized by enzymatic esterification from low quality feedstock which is unrefined and much cheaper than the refined oil, such as palm fatty acid distillate (PFAD) with dialkyl carbonate using immobilized lipase (Novozym®435). Enzymatic process has certain advantages over the chemical process, as it is less energy intensive, allowing the esterification of glycerides with high free fatty acid contents (PFAD, 85-95% FFA) and no enzymatic activity loss. Methanol replaced by dialkyl carbonate, especially DMC due to esterification (methanolysis) is close to equilibrium reaction whereas using DMC the intermediate compound immediately decomposes to carbon dioxide and an alcohol, which have been investigated. Moreover, DMC are cheap, eco-friendly chemical, non-toxic properties and widely available. Factors affecting the reaction such as DMC to PFAD molar ratio, reaction temperature, reaction time and catalyst concentration were systematically analyzed by response surface methodology (RSM) with central composite design (CCD). The optimal condition is using 6:1 molar ratio of DMC to PFAD at 60 oC, for a reaction time 3h in the presence 10wt% of catalyst (based on oil weight). The results showed that synthesis of biodiesel through enzymatic esterification using PFAD suitable for biodiesel production.